Flat bed desiccant dehumidification: A predictive model for desiccant transient characterisation using a species transport model within CFD. (May 2019) - Bonello, M.; Micallef, D.; Borg, S.P.
Abstract: As opposed to steady state characteristics which have been, in the past, estensively investigated, the transient dehumidification characteristics of silica gel under different flat bed configurations, has not been studied in detail with respect to varying mass and air flow rates. Such data is essential in the design of systems employing this method of dehumidification. Moreover, numerical models of the performance of flat bed desiccant configurations generally take the form of fundamental studies with explicit modelling of the desiccant particle geometries. The primary objective of this work aims is to generate dehumidification characteristics in high humidity environments. Secondly, a more simplified and practical approach is proposed here on the basis of experimental calibration. The methodology consists of two main approaches: (i) the development of a test rig for the experimental determination of the transient dehumidification characteristics and, (ii) the development of a Computational Fluid Dynamics (CFD) model using experimental data as input to provide easy extrapolation of experimental data. This paper presents detailed dehumidification results for varying air volume flow rate and desiccant mass. The numerical model, on the other hand, successfully predicts the dehumidification performance of varying silica gel masses by using only a single experimental test case. This proves the validity of using such a model to extrapolate on experimental data. Abstract : Highlights: Changing input air flow rate results in a non-linear change in desiccant saturation. Different masses of desiccant lead to different desiccant saturation characteristics. Development of a numerical model using CFD to predict performance of desiccant.